Toward Understanding the Sex Differences in the Biological Mechanism of Social Stress in Mouse Models - Takahashi, Aki (Frontiers in Psychiatry, 2021)
Significant sex differences in terms of prevalence, symptomatic profiles, severity, and comorbidities of psychiatric disorders are quite common. Women have been shown to be more vulnerable to stress and are nearly twice as likely as men to develop stress-related disorders such as depression and anxiety. Therefore, understanding sex differences with respect to the neurobiological mechanisms underlying stress-related disorders is important for developing more efficient pharmacological interventions for women. However, most preclinical studies on stress-related disorders have focused heavily on male rodents. Here, recent developments in the study of repeated social defeat stress models in female mice are summarized. Our findings suggest that a variety of factors need to be considered when employing this model.